Effect of selected types of warm-up on disjunctive reaction time of soccer goalkeepers - Obetko, M.; Perácek, P.; Mikulic, M.; Babic, M. (Journal of Physical Education and Sport, 2020)
Intensification of the game as one of the development tendencies in soccer is determining what direction we should take in improving players ´ game activities. The aim of our research, but also the training process in soccer, should be the shortening of time needed when making decisions by the implementation of gameactivities. This ability is essential mainly for goalkeepers since the speed of disjunctive reaction time is one of the key factors, which are determining the success rate of goalkeeper ´s interventions. The research group consisted of 24 elite youth soccer goalkeepers (average age 15.6 ±2.4 years). To evaluate the levels of disjunctive reaction time was used a specialized device FiTRO Agility Check. We used the Wilcoxon signed-rank test and Cohen ´s "d" to find out the statistical significance. We found out that the goalkeepers achieved a significant improvement of disjunctive reaction time (p< 0.01) after a specific (match) type of warm-up. Besides we ascertained that the difference between the value of disjunctive reaction time of goalkeepers after the specific (match) or non-specific (athletic) warm-up is 190 ms (p< 0.01). There were found any significant improvement in the values of the disjunctive reaction time (n.s.) after completion of the non-specific (athletic) type of warm-up. Based on our findings, is our recommendation to always during preparation for training or match involve in the warm-up also the specific impulses characteristic for the player position as goalkeeper. It has positive effects not only on values of disjunctive reaction time but also on other motor skills and the overall preparation of soccer goalkeeper ´s organism.